2016
DOI: 10.3803/enm.2016.31.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Novel Molecules Regulating Energy Homeostasis: Physiology and Regulation by Macronutrient Intake and Weight Loss

Abstract: Excess energy intake, without a compensatory increase of energy expenditure, leads to obesity. Several molecules are involved in energy homeostasis regulation and new ones are being discovered constantly. Appetite regulating hormones such as ghrelin, peptide tyrosine-tyrosine and amylin or incretins such as the gastric inhibitory polypeptide have been studied extensively while other molecules such as fibroblast growth factor 21, chemerin, irisin, secreted frizzle-related protein-4, total bile acids, and heme o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 173 publications
(187 reference statements)
0
13
0
Order By: Relevance
“…Ghrelin is mainly produced in cells of the stomach; it induces appetite and thereby controls food intake and energy balance. 12 Plasma levels of ghrelin are inversely correlated with BMI after weight reduction. 13 The major function of ghrelin (the release of growth hormone) is mediated through binding to, and activation of, growth hormone secretagogue receptor type 1a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghrelin is mainly produced in cells of the stomach; it induces appetite and thereby controls food intake and energy balance. 12 Plasma levels of ghrelin are inversely correlated with BMI after weight reduction. 13 The major function of ghrelin (the release of growth hormone) is mediated through binding to, and activation of, growth hormone secretagogue receptor type 1a.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of the aforementioned interaction, molecules released in association with food intake and obesity (eg ghrelin and chemerin) have become a focus of interest. Ghrelin is mainly produced in cells of the stomach; it induces appetite and thereby controls food intake and energy balance . Plasma levels of ghrelin are inversely correlated with BMI after weight reduction .…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin is physiologically food initiation signal. 4 In the research, the mean difference of plasma ghrelin level was not significant between low density group and high density group so it can be concluded that food density did not affect plasma ghrelin level. The results of this study are similar to other study which showed that there was no relationship between ghrelin and macronutrient intake.…”
Section: Discussionmentioning
confidence: 75%
“…The phenomenon of high energy density food consumption such as fast food and sugary foods has become a habit and trend for adolescents in the United States and some Asian countries including Indonesia and causing obesity 3 . The large number of calories and macronutrient composition in the diet shows the effect on hunger, satiety and the desire to eat which is the mechanics of regulating hormones especially ghrelin [4][5][6] . Ghrelin has been recognized to have a major influence on energy balance 7 so that the discovery of various regulatory factors that control ghrelin secretion can have major implications for drug development and diet control 8 In Indonesia the diversity of traditional corn-based foods is advantageous with low energy density, rich in dietary fiber, rich in antioxidants, minerals and excellent for the prevention of degenerative diseases 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol improved insulin resistance, which might be associated with the mitochondrial activity of brown adipocytes. Gavrieli and Mantzoros [61] presented a review of novel molecules regulating energy homeostasis.…”
Section: Articles On Basic Researchmentioning
confidence: 99%